"Fechando pra conta bater": a indigenização dos projetos sociais Xakriabá - Augusta Aparecida Neves de Mendonca (2014)
This thesis is focused for the arrival movement from the social projects to the indigenous people Xakriabá. Referenced in ethnography, discusses the appropriation processes for Xakriabá of numeracy practices that are configured in the defining, in the writing, in the production of speeches, in the engagement, in the development and in the administration of these social projects. These processes of appropriation and their effects are called here of indigenization of the projects. The term indigenization is taken from studies of the anthropologist Marshall Sahlins which refers to the indigenization of the modernity to explain how indigenous peoples how have been developing culturally everything that was inflicted on them and have been trying to incorporate the global system to an even more comprehensive new order: his own world system. When assuming as investigation context the elaboration, the development and the administration of the social projects of Xakriabá, this work turns to the pragmatic aspect that conforms with the numeracy practices which convey dialogues forged in these processes. Such practices involve ideas, values, criteria, concepts or mathematical procedures that mobilize and constitute steps in these projects. The numeracy practices are thus analyzed as a circumstance and not as the object of research. In other words, the investigative exercise to which this study proposes is not configured as a description of practices, but as an analysis of the ways in which these practices convey different rationalities that manage projects and nurture the identification of clashes between rationality from outside and the from within. Such analysis allows to recognize that Xakriabá and those with whom interact in the elaboration processes, development and administration of the projects establishes practices, sometimes submitting to the rules that they are imposed, sometimes transgressing them, dribbling them or transforming them. Thus, indigenize these processes.